If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = r + -4 + 6 Reorder the terms: 0 = -4 + 6 + r Combine like terms: -4 + 6 = 2 0 = 2 + r Solving 0 = 2 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 0 + -1r = 2 + r + -1r Remove the zero: -1r = 2 + r + -1r Combine like terms: r + -1r = 0 -1r = 2 + 0 -1r = 2 Divide each side by '-1'. r = -2 Simplifying r = -2
| 13=u-6 | | -13+12(7)= | | 2(b+3)=14 | | 5p=-8+6p | | 18s-11s-5s=20 | | 4(7s+3)=-15 | | -194-7x=3x+66 | | 2h=1.5h(15*2) | | 54=6+6x | | -4n-4=-56 | | -3s=-135 | | -30+2x=6x+18 | | n*n+8n+2= | | 18=4(s-13) | | (x-8)(4x+2)=10x(x-8) | | 3.69+49=13.6161+7x | | 7v=-350 | | -37-8x=-11x+14 | | 9=3(t+14) | | 7x+16=2x | | 13=-4 | | 8=4(y-18) | | -7x-8=8 | | 5b=-10+6b | | 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 |